Reaching out to fathers in Afro-Caribbean contexts: a case study review of best practices from the Fatherhood is Sacred program in native communities - Hudson, Suzette; Brotherson, Sean E. (Frontiers in Psychology, 2024)
Historical trauma has played a significant role in the difficulties of fathers to fulfill their coparenting roles in Native American communities. This pattern is also true for men in Afro-Caribbean communities. Fatherhood programs developed by the Native American Fatherhood and Family Association (NAFFA) have shown effectiveness in supporting fathers, enhancing their confidence and coparenting skills, and overcoming trauma in Native communities. This paper seeks to identify the opportunities and best practices for cross-cultural adaptation of the Fatherhood is Sacred program to Afro-Caribbean families and contexts.